Treatment of osteoporosis in the solid organ transplant recipient: an organ-based approach - Soumya Kurnool; Nandi Shah; Preethika Ekanayake (Therapeutic Advances in Endocrinology and Metabolism)
Bone and mineral disorders are highly prevalent in solid organ transplant recipients. These patients are at high risk for osteoporosis and fragility fractures due to several pre- and post-transplant factors, including end-stage organ disease leading to chronic malnutrition and osteomalacia, as well as chronic immunosuppressive therapy that has direct adverse effects on bone remodeling. Low pre-transplant bone mineral density is associated with an increased risk for fragility fracture post-transplant. Furthermore, there is a precipitous loss of bone density within 6–12 months post-transplant due to a myriad of causal factors. In this review, we will elaborate on the treatment options and challenges in management of osteoporosis in solid organ recipients using vitamin D, calcium, bisphosphonates, denosumab, and osteoanabolic agents. The greatest body of evidence discusses the use of bisphosphonates, with most patients benefiting from early treatment.